ANALISIS PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN - Muiz, Abdul; Muchsinati, Evi Silvana (Journal of Accounting and Management Innovation, 2017)
The focus of this study is to measure the effect of human resource management practice in the employees of hotel sector in Batam City. Samples were taken from 299 hotel employees of 5 a four-star hotel in the district of Batu Ampar. The Research data that has been collected is analyzed using Partial Least Squares Path Modelling (PLS-SEM) program version 3. Results from this study showed first, recruitment has a significant effect on employee performance. Second, the selection has a significant effect on employee performance. Third, the training doesn’t have a significant effect on employee performance. Fourth, compensation doesn’t have a significant effect on employee performance. Fifth, promotion doesn’t have a significant effect on employee performance.Keywords: Recruitment, Selection, Training, Compensation, Promotion, and Employee Performance.